How does experience influence game reasoning?: a survey for repeated prisoner’s dilemma - Fang, Tong (2023)
This dissertation reviews past literature on belief updating/belief-based learning and sophistication (reasoning), links the two models with recent experimental findings in repeated prisoner’s dilemma, supergame strategies, attention and incentives, and tries to answer how these two models interact with each other with experience. These two models have good performance in explaining part of the repeated games separately but fail to a smooth and united explanation. By re-examining the literature from the perspective of the information source to generate different types of belief, elements of two models can be reconciled into one. Recent new findings in attention and incentives also contribute to the evolution of sophistication, which was not captured by the sophistication models. This helps to examine sophistication models in a dynamic way and makes both models comparable from the dynamic point of view.